Relative Positions of the Polar Boundary of the Outer Electron Radiation Belt and the Equatorial Boundary of the Auroral Oval - Stepanova, M (Copernicus GmbH, 2018)
Finding the position of the polar boundary of the outer electron radiation belt, relative to the position of the auroral oval, is a long-standing problem. Here we analyze it using the data of the METEOR-M1 auroral satellite for the period from 11 November 2009 to 27 March 2010. The geomagnetic conditions during the analyzed period were comparatively quiet. METEOR-M1 has a polar solar-synchronous circular orbit with an altitude of ĝ‰ 832 km, a period of 101.3 min, and an inclination of 98°. We analyze flux observations of auroral electrons with energies between 0.03 and 16 keV, and electrons with energies > 100 keV, measured simultaneously by the GGAK-M set of instruments, composed of semiconductors, scintillator detectors, and electrostatic analyzers. We assume that in the absence of geomagnetic storms the polar boundary of the outer radiation belt can be identified as a decrease in the count rate of precipitating energetic electrons to the background level. It was found that this boundary can be located both inside the auroral oval or equatorward of the equatorial boundary of the auroral precipitation. It was also found that for slightly disturbed geomagnetic conditions the polar boundary of the outer radiation belt is almost always located inside the auroral oval. We observe that the difference between the position of the polar boundary of the outer radiation belt and the position of the equatorial boundary of the auroral precipitation depend on the AE and PC indices of geomagnetic activity. The implications of these results in the analysis of the formation of the outer radiation belt are discussed. © Author(s) 2018.